Chemical Characterisation and Biorefinery Efficiency of Timothy Grass and Pulp Silages - Ayanfe, Nisola; Franco, Marcia; Jalava, Taina; Stefanski, Tomasz; Rinne, Marketta (Wiley-Blackwell, 2025)
This study investigated the effects of increased dry matter concentration by screw-pressing or wilting and additive application on fermentation quality of primary growth (PG) and first regrowth (ReG) timothy grass. Additionally, the nutritional quality of the liquid produced during the screw-pressing of pre-ensiled and ensiled biomasses was assessed. Two experiments were conducted: PG grass (Experiment 1) was ensiled fresh (Intact) and following liquid extraction via screw-pressing of fresh biomass (Pulp), whilst ReG included wilted biomass in addition to Intact and Pulp (Experiment 2). Biomasses were ensiled without any additives (Control), with lactic acid bacteria inoculant (LAB), or with a formic acid-based additive (FA). The PG biomasses were ensiled in vacuum bags and ReG in laboratory-scale cylindrical silos for 3 months. The silages were subjected to screw-pressing, and the chemical composition of the liquid was analysed. In both experiments, the Pulp had reduced water-soluble carbohydrates and ash compared to the Intact biomass, but crude protein concentration was not affected. In Experiment 2, pulping and wilting improved ensilability. Silages in both experiments exhibited good fermentation quality, with low pH and ammonia nitrogen concentration. Additionally, FA further reduced protein degradation. Wilting restricted silage fermentation, resulting in slightly elevated pH and reduced lactic acid production, alongside decreased ethanol production. Additives improved fermentation quality in different ways; LAB decreased the pH in wilted silages, and FA initiated fibre hydrolysis, leading to an increase in water-soluble carbohydrate concentration, which surpassed levels present in the raw material. In Experiment 2, ensiling increased liquid yield and protein capture into the liquid fraction compared to fresh biomass. Screw-pressing silage treated with LAB increased crude protein concentration in the liquid whilst FA reduced it. Different processing methods demonstrated possibilities to vary feedstock composition for biorefineries, which can be optimised based on the target end products.
Keywords: harvest timing; formic acid; microbial inoculant; anaerobic fermentation; fractionation; feed preservation